Infection with the Lyme disease pathogen suppresses innate immunity in mice with diet‐induced obesity. (25th November 2016) - Zlotnikov, Nataliya; Javid, Ashkan; Ahmed, Mijhgan; Eshghi, Azad; Tang, Tian Tian; Arya, Anoop; Bansal, Anil; Matar, Fatima; Parikh, Maitry; Ebady, Rhodaba; Koh, Adeline; Gupta, Nupur; et al.
Abstract: Obesity is a major global public health concern. Immune responses implicated in obesity also control certain infections. We investigated the effects of high‐fat diet‐induced obesity (DIO) on infection with the Lyme disease bacterium Borrelia burgdorferi in mice. DIO was associated with systemic suppression of neutrophil‐ and macrophage‐based innate immune responses. These included bacterial uptake and cytokine production, and systemic, progressive impairment of bacterial clearance, and increased carditis severity. B. burgdorferi ‐infected mice fed normal diet also gained weight at the same rate as uninfected mice fed high‐fat diet, toll‐like receptor 4 deficiency rescued bacterial clearance defects, which greater in female than male mice, and killing of an unrelated bacterium ( Escherichia coli ) by bone marrow‐derived macrophages from obese, B. burgdorferi ‐infected mice was also affected. Importantly, innate immune suppression increased with infection duration and depended on cooperative and synergistic interactions between DIO and B. burgdorferi infection. Thus, obesity and B. burgdorferi infection cooperatively and progressively suppressed innate immunity in mice.